From Flash and Fire Points of Water Miscible Flammable Liquid Mixtures to a Novel Method of Membrane Characterization - Sabri, Waseem (Université d'Ottawa / University of Ottawa, 2022)
The National Fire Code and the National Building Code are two complimentary documents that outline the requirements for constructing or demolishing buildings and facilities in Canada. Part 4 of the fire code revolves around the storage, handling, building material requirements, leak detection systems, and piping requirements, among many other factors that must be considered for flammable and combustible materials. The codes consider a water-miscible flammable liquid (WMFL) mixture to be the same risk as a pure flammable liquid which intuitively is known to be incorrect. Diluting a flammable liquid with water will lower the fire safety risk by increasing the flash and fire point. Depending on the flash point, fire point, kinematic viscosity and boiling point, flammable liquids are placed into specific risk categories. Intuition itself is not enough to exclude WMFL mixtures from the pure flammable liquid category. Therefore a new category must be created by experimentally obtaining the flash point, fire point, kinematic viscosity and boiling point of WMFL mixtures. The results of this project allowed for quantification of the expected trends and might be used to justify changing the categorization of WMFL mixtures in the codes. Improved gas separation membranes require developing new membrane materials, typically synthetic polymers. In turn, it requires their accurate characterization. Membrane characterization, i.e. obtaining the fundamental transport properties of the membrane material, is usually done using the time lag method in a constant volume system. The time-lag method allows the determination of the permeability, diffusivity and solubility in polymeric gas separation membranes from a single dynamic gas permeation experiment. The time lag method involves exposing a membrane that is originally degassed to a sudden increase in pressure upstream of the membrane. The rate of pressure increase in the downstream receiving volume is monitored, which produces a pressure rise curve which can be used to extract the membrane properties. For the complete characterization of glassy polymer membranes, multiple time lag experiments are required at varying pressures. A novel time-lag protocol is proposed based on a series of step changes in the feed pressure (steps up followed by steps down), equivalent to multiple time lag experiments. Unlike the classical time-lag protocol, the initial condition for the characterized membrane in the new protocol is a linear concentration profile within the membranes instead of a uniform, zero concentration across the membrane. Preliminary results in this project indicate the feasibility of the proposed new protocol.